América Latina : aspectos principales del financiamíento externo - Massad A., Carlos (Estudios Internacionales, 1983)
In recent years, Latin America has shown large imbalances in its external accounts, perhaps the largest in history. A situation like this is sustainable only if three conditions are met: a) That the resources of foreign savings be used together with national savings to expand the country’s productive capacity; b) That the external economic environment does not experience significant negative fluctuations that decrease the ability to pay the debt or increase the burden of servicing it; and c) That the flow of external financial resources does not have abrupt interruptions. However, none of these three conditions to sustain the current account and capital imbalances in Latin America has been fully met, which forces the adjustment and financing needs of Latin American countries.